10. KEGAGALAN CALEG PETAHANA DALAM PILEG DPRD JAWA TENGAH 2014 - Wahid Abdulrahman (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2015)
Legislative incumbent candidates have a chance to win the legislative elections with the political capital that they have been owned. However, the fact is that 32 of the 69 legislative incumbent candidates have been failed to be re-elected in 2014 election for Central Java House of Representative. Through a qualitative approach this study explains the failure of legislative incumbent candidates in 2014 Central Java house of representative. The results show incumbent candidate reasons of failure is the failure of the party in maintaining the seat, the inability of incumbent candidates in facing internal competition with other candidates in one party, and the serial number. Pragmatism voters, election less professional organizers are all factors that contribute to the defeat of incumbent candidates.